2013
DOI: 10.1130/b30693.1
|View full text |Cite
|
Sign up to set email alerts
|

Deriving a long paleoseismic record from a shallow-water Holocene basin next to the Alpine fault, New Zealand

Abstract: A sedimentary sequence that was highly sensitive to fault rupture-driven changes in water level and sediment supply has been used to extract a continuous record of 22 large earthquakes on the Alpine fault, the fastest-slipping fault in New Zealand. At Hokuri Creek, in South Westland, an 18 m thickness of Holocene sediments accumulated against the Alpine fault scarp from ca. A.D. 800 to 6000 B.C. We used geomorphological mapping, sedimentology, and paleoenvironmental reconstruction to investigate the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 67 publications
(76 reference statements)
1
10
0
Order By: Relevance
“…7) of the peat unit 4; (2) changes in the depositional environment (change from a quiet unit 4 peat to a more energetic alluvial environment unit 5 sand); and (3) the unconformity between units 4 and 5 to the north of T-2. Our interpretation, which relies on the changes in depositional environment as earthquake proxies, is consistent with the work of other researchers (e.g., Cowan and McGlone, 1991;Berryman et al, 2012;Clark et al, 2013).…”
Section: Missing Earthquake Events?supporting
confidence: 93%
“…7) of the peat unit 4; (2) changes in the depositional environment (change from a quiet unit 4 peat to a more energetic alluvial environment unit 5 sand); and (3) the unconformity between units 4 and 5 to the north of T-2. Our interpretation, which relies on the changes in depositional environment as earthquake proxies, is consistent with the work of other researchers (e.g., Cowan and McGlone, 1991;Berryman et al, 2012;Clark et al, 2013).…”
Section: Missing Earthquake Events?supporting
confidence: 93%
“…Whereas a >2,000-year-long paleoearthquake record has been documented for the Alpine fault [Berryman et al, 2012b;Howarth et al, 2012Howarth et al, , 2014Howarth et al, , 2016Clark et al, 2013;Cochran et al, 2017;see Howarth et al, 2018 for review], the paleoearthquake record of the Conway segment of the Hope fault is not well documented beyond an approximate age of the most recent event [Langridge et al, 2003]. In this study, we document and provide age constraints for at least the five most recent events along the Conway segment.…”
Section: Introductionmentioning
confidence: 87%
“…To complete plate boundary system earthquake behavior analysis, we study the fastestslipping strike-slip faults of the Australian-Pacific plate boundary of the northern South Island and southern North Island of New Zealand, where previous studies have documented patterns of earthquake recurrence on many of these major faults [e.g., Cooper and Norris, 1990;Wells et al, 1999;Langridge et al, 2003Langridge et al, , 2013Mason et al, 2006;Sutherland et al, 2007;Little et al, 2009;Van Dissen and Nicol, 2009;Berryman et al, 2012aBerryman et al, , 2012bDe Pascale and Langridge, 2012;Howarth et al, 2012Howarth et al, , 2014Howarth et al, , 2016Clark et al, 2013Clark et al, , 2015Nicol et al, 2016;Khajavi et al, 2016;Cochran et al, 2017;Nicol and Dissen, 2018]. The Hope fault, the subject of this manuscript, is the central link between high slip-rate faults to the southwest (Alpine fault) and northeast (Jordan-Kekerengu-Needles fault and the Wairarapa fault in southern North Island).…”
Section: Introductionmentioning
confidence: 99%
“…The Alpine Fault generates coseismic landslides that provide pulses of sediments to the local catchments (e.g. Howarth et al 2012;Clark et al 2013). These sediments are then transported to the Tasman Sea (Figs.…”
Section: Site Description and Survey Methodologymentioning
confidence: 99%
“…A number of studies have concluded that large Alpine Fault events result in large pulses of sediment (e.g. Berryman et al 2012;Clark et al 2013;Howarth et al 2012), which are efficiently delivered to the catchments during large rainfall events (Fitzsimons et al 2013). Coastal areas of these catchments record the large rainfall, landslide, and faulting events as pulses of sediments that are redistributed by long-shore transport and then by wave and wind action to form coastal dunes, which are subsequently populated by trees and shrubs within decades of an event Goff 2006, 2007).…”
Section: Introductionmentioning
confidence: 99%